Surveying the Importance of Population and its Demographic Profile, Responsible for the Evolution of the Natura 2000 Sites of Bihor County, Romania - Linc, Ribana; Dinca, Iulian; Corina Tatar, Marcu; Bucur, Liviu (Eastern European Countryside, 2024)
The current study focuses on the demographic profile research of Nature 2000 sites belonging to 28 administrative entities located in Bihor County, in northwestern Romania. For the purposes of this study, out of the 74 local administrative units (LAUs) holding protected areas of the type Nature 2000 while only sites that cover over 40% of the administrative entities’ area were taken into account. Starting from the interrelation of the contact between human communities and local ecosystems, the research sought to determine the interdependence level between the local residents’ lifestyle and the biodiversity-related maintenance/ preservation of these protected areas. Based on the referenced statistics, more demographic indicators were calculated (population decrement, population density, structure by age, dependency index, active population and structure by industry) and basic indicators of pressure on the environment (naturality index, human pressure through land use and forest area per capita). Each of these factors are meant to reveal how man cohabitates with nature in a balanced or disrupted manner according to the study results. Thus, considering the 28 LAUs from case to case, areas where environmental health tends to insecurity were identified, but there are cases in which it is satisfactory thanks to the existence of massive woodlands over wide areas, while also being due to a considerable demographic decrement.